2018
DOI: 10.1371/journal.pone.0202805
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risks in female cancer survivors: A population-based analysis

Abstract: Background/objectivesAdvances in cancer management have resulted in improved survival rates, particularly in children and young adults. However, treatment may adversely affect reproductive outcomes among female cancer survivors. The objective of this study was to investigate their risk of adverse perinatal outcomes compared to the general population.Design/methodsWe performed a population-based analysis, including all female cancer survivors diagnosed before the age of 40 years between 1981 and 2012. Pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
3
38
1
Order By: Relevance
“…There were five studies that reported on the incidence of spontaneous vaginal deliveries, in total reporting on 3,497 cancer survivors and 24,370 controls [12,13,23,24,28]. In the random effect model, cancer survivors were equally likely to have a spontaneous vaginal delivery: relative risk was 0.95 (95% CI 0.84 -1.07) ( Figure 3A).…”
Section: Spontaneous Vaginal Deliverymentioning
confidence: 99%
See 4 more Smart Citations
“…There were five studies that reported on the incidence of spontaneous vaginal deliveries, in total reporting on 3,497 cancer survivors and 24,370 controls [12,13,23,24,28]. In the random effect model, cancer survivors were equally likely to have a spontaneous vaginal delivery: relative risk was 0.95 (95% CI 0.84 -1.07) ( Figure 3A).…”
Section: Spontaneous Vaginal Deliverymentioning
confidence: 99%
“…Five studies with in total 5,471 survivors and 45,593 controls reported the incidence of emergency caesarean sections in their cohorts [9,12,13,27,28]. The relative risk was 1.22 (95% CI 1.15 -1.30) ( Figure 3C).…”
Section: Emergency Caesarean Sectionmentioning
confidence: 99%
See 3 more Smart Citations